Vivencias y percepciones de mujeres que Tuvieron la experiencia de un parto vertical en La comunidad nativa de Aucaloma - provincia de Lamas, Junio – Diciembre 2014 - Velásquez Ramírez, Cynthia Mabel (2015)
This research aimed to analyze the experiences and perceptions of women who had The experience of a vertical delivery in the Native Community of Aucaloma province of Lamas; from June to December 2014. Qualitative study whose methodology was Depth interviews; The data collection instrument was a questionnaire with semistructured Interview. The study resulted in: women showed no difference between the perception of pain And the time dilation relative to labor; but they expressed with certainty that vertical Births are much more beneficial than the horizontal deliveries, in terms of participation Of the same woman in labor in labor, family or partner and the duration of labor. Also, An association between the vertical birth and home birth in the Native Community of Aucaloma, as a traditional way of happening of motherhood; most women did not Identify disadvantages of vertical delivery for both mother and baby; and show more Advantages: not having experienced childbirth complications, difficulties, suffering or Pain; and little bleeding, convenience and speed; women not seeking care delivery in The health center say they do not because their customs are not respected. In conclusion: a simple way women Native Community of Aucaloma identified Important benefits when they expressed satisfaction, comfort, speed, no problem, that Sums up all that is known in other studies as advantages of traditional birth upright.